In vitro anti‐inflammatory and antioxidant activities of ZnFe2O4 and CrFe2O4 nanoparticles synthesized using Boswellia carteri resin. Issue 6 (20th April 2021) - Imraish, Amer; Abu Thiab, Tuqa; Al‐Awaida, Wajdy; Al‐Ameer, Hamzeh J.; Bustanji, Yasser; Hammad, Hana; Alsharif, Mays; Al‐Hunaiti, Afnan
Abstract: The development of plant‐based nano‐materials is considered an eco‐friendly technology because it does not involve hazardous chemicals. In this study, bimetallic ZnFe2 O4 and CrFe2 O4 nanoparticles were synthesized using an aqueous extract of Boswellia carteri resin. Synthesized ZnFe2 O4 and CrFe2 O4 nanoparticles were characterized by UV‐Vis spectroscopy, FTIR, XRD, and HR–TEM. The anti‐inflammatory activity was investigated in LPS‐stimulated RAW 264.7 macrophages, whereas antioxidant activity was examined using a Hydrogen Peroxide Scavenging Activity Assay, Nitric Oxide Scavenging Activity Assay, and ABTS Radical Scavenging Assay. ZnFe2 O4 and CrFe2 O4 nanoparticles demonstrated a moderate scavenger of H2 O2 with IC50 values; 87.528 ± 8 μg/ml and 146.4468 ± 12 μg/ml, respectively. While they exhibited a strong scavenger of NO with IC50 values; 4.01 ± 0.7 μg/ml and 4.01 ± 0.7μg/ml, respectively. Interestingly, ZnFe2 O4 and CrFe2 O4 nanoparticles revealed an excellent anti‐inflammatory activity by dose‐dependently suppressing mRNA expressions of IL‐1b, IL‐6, and TNF‐α. Also, ZnFe2 O4 and CrFe2 O4 nanoparticles suppress the protein expression of TNF‐α. Together, our results proved that phyto‐mediated ZnFe2 O4 and CrFe2 O4 nanoparticles using Boswellia carteri resin have great potential in biomedical applications such as anti‐inflammatory and antioxidant. Practical applications: Our phyto‐synthesized chromium iron oxide bimetallic nanoparticles (NPs) have shown a novel and potent anti‐inflammatory activity, with remarkable biosafety toward tested macrophages. Zinc iron oxide bimetallic NPs exhibited anti‐inflammatory effect with a lesser extent compared to the former, with moderate cytotoxicity against tested macrophages. Both zinc and chromium iron oxide NPs exhibited an equivalent antioxidant activity. Our resin‐capped chromium iron oxide NPs are suggested to be a competing nonsteroidal anti‐inflammatory agent; it is further recommended to establish advanced animal studies to confirm their biosafety, stability, and anti‐inflammatory activity accompanied with the antioxidant activity. Abstract : ZnFe2 O4 and CrFe2 O4 nanoparticles demonstrated a moderate scavenger of H2 O2 with IC50 values; 87.528 ± 8 μg/ml and 146.4468 ± 12 μg/ml, respectively. While they exhibited a strong scavenger of NO with IC50 values; 4.01 ± 0.7 μg/ml and 4.01 ± 0.7μg/ml, respectively. Interestingly, ZnFe2 O4 and CrFe2 O4 nanoparticles revealed an excellent anti‐inflammatory activity by dose‐dependently suppressing mRNA expressions of IL‐1b, IL‐6, and TNF‐α. Also, ZnFe2 O4 and CrFe2 O4 nanoparticles suppress the protein expression of TNF‐α.